n-Butanolic fraction of endofitic fungi of Buah Makasar increases apoptotic effect of doxorubicin on MCF-7 cells - Meiyanto, Edy; Kumala, Shirly; Septisetyani, Endah Puji (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2009)
Makassar fruit, Brucea javanica (L.) Merr., showed chemopreventive activity. Secondary metabolites come from B. javanica fruit, brucatol and bruceantine, induced cell differentiation and apoptosis on Leukemia cell, while quassinoid and its derivates acted as antitumor promoter. Butanolic fraction of supernatan of endofitic fungi 1.2.11 isolate fermentation which isolated from B. javanica fruit showed cytotoxicity toward several cancer cells. This fraction has been predicted contain secondary metabolites from B. javanica and has been identified as Bruceosin and Canthin-6-one derivates. Butanolic fraction (FB) of supernatan from endofitic fungi 1.3.11 isolate fermentation is predicted for having similiar cytotoxycity as active as 1.2.11 isolate. This research is aimed to explore cytotoxycity potention dan doxorubicin on MCF-7 breast cancer cell.Synergism of BF-doxorubicin combination detect from cell viability inhibition and apoptosis induction on MCF-7, a breast cancer cell lines which shows resistancy toward doxorubicin. Cell viability on single treatment of FB and doxorubicin and its combination were carried out by MTT assay to determine IC50 and combination index (CI). Apoptosis induction of FB, doxorubicin and its combination were carried out by ethidium bromideacridine orange DNA staining.n- Butanolic fraction and doxorubicin showed cell viability inhibition on MCF-7 cell with IC50 48 μg/mL and 148 nM, respectively. Both of FB and doxorubicin showed apoptosis induction on IC50. Combination of FBdoxorubicin showed synergism and increased apoptosis induction on MCF-7 cell.Key words: Brucea javanica, endofitic fungi, MCF-7 cell, synergism, doxorubicin.